Zastosowanie synchronizowanych okien czasowych do wyznaczania mocy czynnej na podstawie próbek = Application of synchronized time windows for evaluation of active power based on samples - Kłosiński, Radosław; Jurojć, Tomasz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The object of the work is to compare algorithms for determining active power on the basis of voltage and current samples in the time and frequency domain, without and using synchronized windows and modified discrete Fourier transform (MDFT). The results of numerical experiments show a great improvement in accuracy as a result of using synchronized windows.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne